To solve for x and y in this system of equations, we can use substitution or elimination.
Let's use the substitution method:
1. Solve the first equation for y:
y = -3/2x - 2
2. Substitute y = -3/2x - 2 into the second equation:
2x - (-3/2x - 2) = -5
2x + 3/2x + 2 = -5
(4/2)x + (3/2)x + 2 = -5
(7/2)x + 2 = -5
(7/2)x = -7
x = -7 * (2/7)
x = -2
3. Substitute x = -2 back into the first equation to solve for y:
y = -3/2(-2) - 2
y = 3 + 2
y = 5
Therefore, the solution to the system of equations is x = -2 and y = 5.
y = -3/2x -2
2x - y = -5
3 answers
x - 4y = 8, 3x + 10 = -2y
To solve for x and y in this system of equations, we can use the substitution or elimination method:
Let's use the substitution method:
1. Solve the second equation for y:
3x + 10 = -2y
-2y = 3x + 10
y = (-3/2)x - 5
2. Substitute y = (-3/2)x - 5 into the first equation:
x - 4((-3/2)x - 5) = 8
x + 6x + 20 = 8
7x + 20 = 8
7x = -12
x = -12/7
3. Substitute x = -12/7 back into the second equation to solve for y:
3(-12/7) + 10 = -2y
-36/7 + 10 = -2y
-36/7 + 70/7 = -2y
34/7 = -2y
y = -17/7
Therefore, the solution to the system of equations is x = -12/7 and y = -17/7.
Let's use the substitution method:
1. Solve the second equation for y:
3x + 10 = -2y
-2y = 3x + 10
y = (-3/2)x - 5
2. Substitute y = (-3/2)x - 5 into the first equation:
x - 4((-3/2)x - 5) = 8
x + 6x + 20 = 8
7x + 20 = 8
7x = -12
x = -12/7
3. Substitute x = -12/7 back into the second equation to solve for y:
3(-12/7) + 10 = -2y
-36/7 + 10 = -2y
-36/7 + 70/7 = -2y
34/7 = -2y
y = -17/7
Therefore, the solution to the system of equations is x = -12/7 and y = -17/7.